(untitled) (Veterinary Science, 2017)
The primary objective of the work was to determine and standardize the ultrasonographic use of ecographi in the gonads bull in order to evaluate it anatomically. The secondary objectives were to determine if there is any individualvariation by ultrasound observed through reproductive activities, age and environmental condition among individuals evaluated; and determine if there is any significant variability between individuals within the sample through the lasting time of the project. It utilised five different planes to each individual to live animals under pastoral conditions and it settled the most convenient. Fifteen Hereford bulls were evaluated in six opportunities, starting at 24 month of age during two years, autumn, winter and spring. During summer were unable to take any determination because the animals were under natural meeting. Each bull was evaluated to determine variability through the study-period, body condition, and body condition pre- and post-mating. Using different ultrasound cut was able to evaluate and characterise the scrotum, testicular parenchyma, pampiniform plexus and head, body and epididimun cauda.